Green Synthesis Silver Nanoparticles Using Sembung (Blumea balsamifera) Leaf Extract as an Antibacterial and Antioxidant - I Wayan Tanjung Aryasa; Ni Putu Rahayu Artini (Jurnal Penelitian Pendidikan IPA, 2023)
Silver Nanoparticles essentially focuses on the synthesis of nano-sized particles produced through chemical, physical and biological processes, which contribute significantly to the control of plant and animal diseases and have shown considerable promise in improving the quality of living conditions and human health. Currently, silver nanoparticles (AgNP) have shown their potential as an alternative antibacterial and antioxidant agent in many studies. The method for making silver nanoparticles, namely Green synthesis, involves the use of plants for the synthesis process of various types of nanoparticles. Green synthesis has the advantages, namely that the method is simple, environmentally friendly, non-polluting, antitoxic and cost-effective. The aim of this research is to determine the antibacterial and antioxidant activity of AgNPs. In this research, the nanoparticle solution was visually determined by the yellow-brown color change. In the spectrophotometer absorption spectrum appears at a wavelength of 425 nm. The results of determining the size distribution of silver nanoparticles using PSA show that the particle size distribution obtained has an average value of 40.5 nm and 59.6 nm for silver nanoparticles for AgNO3 concentrations of 1 mM and 2 mM, respectively. FTIR measurements are used to determine the presence of bioactive molecules that may be responsible for the stabilization that acts as a capping agent. Absorption spiked at 3.280; 2.919; 1.583; 1.379; 1.239 and 1.068 cmâˆ’1 were determined for sembung leaf extract, while silver nanoparticles showed an absorption spike at 3.368; 2.850; 1.594; 1.369; 1.244 and 1.108 cmâˆ’1. The results of XRD analysis of AgNP show that it has been successfully synthesized which can be seen from the formation of a narrow peak indicating the crystalline nature of the nanoparticles formed. The results of TEM analysis of AgNPs in this study are mixed shapes such as spherical, hexagonal and triangular shapes of silver nanoparticles. The antibacterial activity test of silver nanoparticles with sembung leaf extract with varying concentrations of AgNO3 solution was successful as indicated by the formation of an inhibition zone for Eschericia coli and Staphylococcus aureus bacteria. The results show that the antioxidant activity of AgNPs shows that the percentage of inhibition increases as the concentration of AgNPs increases from 100 to 500 ppm and ascorbic acid increases from 1 to 5 ppm.